Implementation of the Design for Change (DFC) Method through Project-Based Learning in Developing Intrapersonal and Interpersonal Skills of Islamic Religious Education Students - Asniyah Nailasariy; Burhan Yusuf Habibi; Khodijatul Kubro; Nurhaliza; Aisyah Rahayu Setyaningrum (Jurnal Pendidikan Agama Islam, 2023)
Purpose – This study aims to describe the implementation of the Design for Change (DFC) method in the Softskill Education course to improve the soft skills of PAI students at UIN Sunan Kalijaga. One of the reasons for the moral and character crisis that occurs among students is the lack of maximum internalization of values in learning. Aspects of affection should be accommodated to develop honest, tolerant, adaptive attitudes, and a number of other attitudes. This is where it is important to carry out soft skills learning for PAI teacher candidates with a project-based learning approach, in order to be able to improve personal and social competence, and in the future be able to apply this method to future students. Design/methods/approach – This study uses a qualitative approach with a descriptive method, where the researcher attempts to describe the process and results of the application of the DFC method. Researchers conducted a series of techniques in data collection, there are observation, documentation, and interviews. The research instrument is the researcher himself. Determination of sample data sources using a purposive sampling technique. Data analysis was carried out descriptively, where the data that had been collected was critically analyzed in depth by means of data triangulation with the steps of data collection, data sorting, data presentation, and conclusion presentation. Findings – The results of this study indicate that the implementation of the DFC method, with four-step formulations namely FIDS (Feel, Imagine, Do, and Share) is considered quite effective in improvthe ing soft skills of PAI students. So far, no research has been conducted using this method to be applied to PAI students, so the results of this study are considered important as an effort to equip attitude competence to prospective PAI teachers. Soft skills developed by students include intrapersonal and interpersonal skills, including; confidence, leadership, self and time management, adaptability, and public speaking. Even though there are several obstacles in its application, related to the cycle being too short, and the lack of student motivation, all respondents said that the benefits of this method can be felt and applied in a sustainable manner. Research implications/limitations – The data sources are limited to the students of PAI at UIN Sunan Kalijaga class of 2018 who in 2021 are taking Softskill Education courses. Originality/value – The findings of this study provide an overview of methods that can be applied in developing soft skills in Islamic Religious Education students.